Transfer sheet for mark-forming member using ultraviolet laser
By using transfer sheets of fluorocarbon polymers and polyisocyanate compounds, and combining ultraviolet lasers to form high-temperature and acid-base-resistant marking layers, the problem of unstable existing marking members in high-temperature or strong acid-base environments is solved, and stable printing of high-density information is achieved and simplified production is achieved.
Patent Information
- Application Number
- JP2023122034
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-07-26
- Publication Date
- 2025-02-06
AI Technical Summary
The existing mark formation members are not chemically resistant enough in high temperature or strong acid and alkali environments, and it is difficult to print high-density information such as QR codes stably during the manufacturing process, and the production process is complex and the equipment load is large.
A transfer sheet containing fluorocarbon polymer with a fluorine content of more than 10% and a polyisocyanate compound containing hydroxyl groups is used to form a marking layer in combination with ultraviolet laser, and a transparent protective layer and a metal oxide are used to form a high temperature resistant and acid-base-resistant label forming member.
The ability to print high-density information stably in high-temperature or strong acid-base environments is realized, simplifying the production process and improving the chemical and heat resistance of the equipment.
Smart Images

Figure 2025018381000001
Abstract
Description
[Technical field]
[0001] The present invention relates to a transfer sheet for a mark-forming member capable of recording advanced information used from the standpoint of process management and traceability of manufactured goods, and in particular to a transfer sheet for a mark-forming member on which a mark has been formed, which can then be used in fields requiring advanced chemical resistance, heat resistance, and weather resistance. [Background technology]
[0002] In recent years, as a marking system, particularly in the field of food packaging materials, a marking system that uses the discoloration of titanium oxide or the like by irradiating an ultraviolet laser onto a film layer containing titanium oxide or the like in resin (for example, Patent Document 1, etc.) has been attracting attention. It is believed that the discoloration of titanium oxide occurs when the ionic valence of titanium oxide contained in the layer changes and oxygen defects occur, changing from white to black or the like, which makes it visible. It is believed that the ionic valence of titanium oxide changes when it is irradiated with light energy corresponding to the band gap of titanium oxide. The band gap of titanium oxide varies depending on the crystal system, but is generally about 3.0 to 3.2 eV, and the wavelength of light corresponding to this is 420 nm or less. Therefore, it is difficult to cause discoloration due to the change in ionic valence of titanium oxide even if a laser beam with a wavelength exceeding 420 nm (for example, 532 nm, 1064 nm) is used. As a result, the ultraviolet laser marking system has the advantage that it is less likely to cause changes in the physical shape of the recorded area, i.e., unevenness, compared to laser thermal etching methods, and is a method suitable for high-density information recording.
[0003] In the manufacturing process of manufactured goods, etc., there is an increasing demand for a system capable of printing advanced information such as two-dimensional codes on labels and tags used for process management. In this regard, the ultraviolet laser marking system is a suitable system.
[0004] However, depending on the manufactured product, the label or tag after marking may be exposed to a strong alkaline or strong acidic aqueous solution at high temperatures. For example, the surface treatment process of galvanized steel sheet products includes a degreasing process and an acid pickling process for the steel sheet. In general, the degreasing process may be performed with an aqueous solution of caustic soda with a concentration of 5 to 10% by weight, at a temperature of 50 to 85°C, and for an immersion time of about 60 minutes, while the acid pickling process may be performed with an aqueous solution of hydrochloric acid with a concentration of 10 to 20%, at a temperature of 20 to 50°C, and for an immersion time of about 150 minutes. In addition, the process of forming a black oxide film as an anti-rust treatment for steel may be performed under even harsher conditions (aqueous solution of caustic soda with a concentration of 35 to 50% by weight, at a temperature of 90°C or higher, and for an immersion time of 60 minutes or longer). In addition, depending on the surface treatment process of the manufactured product, the product may be exposed to a high temperature of 200°C or higher.
[0005] However, at present, no mark-forming member that is fully satisfactory as a mark-forming member for process control when used in a process in which the material is immersed in a strong alkaline or strong acidic aqueous solution at such high temperatures has yet been obtained.
[0006] On the other hand, outside the field of packaging materials, Patent Document 2 describes a fluororesin-coated material in which a metal oxide or metal hydroxide whose color tone changes as its oxidation number is changed by irradiation with an excimer laser, which is an ultraviolet laser, is dispersed or formed in order to form marks such as scales, patterns, and characters on the inner pot of a rice cooker, and a method for producing the same.
[0007] Fluororesin is a resin that has excellent chemical resistance, heat resistance, weather resistance, stain resistance, etc., and the fluororesin-coated material in which a metal oxide whose color tone changes depending on the oxidation number is dispersed or formed is expected to be used as a label or tag for process management and traceability.
[0008] However, the manufacturing method of providing the fluororesin coating on an adherend such as a metal described in Patent Document 2 is a method of forming a fluororesin coating by coating a mixture of the fluororesin particles and metal oxide particles, the color tone of which changes depending on the oxidation number, dispersed in water, by a coating method, drying, and then baking (Example: treatment at 420°C for 20 minutes). In such a manufacturing method of the fluororesin coating by a high-temperature baking method, a heating facility at or above the melting point of the fluororesin (about 320°C) is required to manufacture the labels or tags, which has the problem of placing a heavy load on the manufacturing facility. In addition, because it is a coating method, when the mark formation surface is a curved surface or the like, it is necessary to perform bending or pressing of the mark formation member after providing the fluororesin coating or after forming a mark on the coating, which is extremely troublesome. [Prior art documents] [Patent documents]
[0009] [Patent Document 1] JP 2020-78924 A [Patent Document 2] Japanese Patent Application Publication No. 6-100716 Summary of the Invention [Problem to be solved by the invention]
[0010] In view of the above background, an object of the present invention is to provide a transfer sheet for a mark-forming member using an ultraviolet laser, which enables high-density information recording such as two-dimensional codes using an ultraviolet laser, has excellent chemical resistance, heat resistance, weather resistance, stain resistance, etc. after mark formation, and allows the use of substrates with a high degree of freedom in type and shape, and can easily produce a mark-forming member. [Means for solving the problem]
[0011] The means for achieving the object of the present invention will be specifically described below.
[0012] The first invention is a transfer sheet for a mark-forming member using an ultraviolet laser, characterized in that it comprises a transparent protective layer peelably provided on a thermoplastic resin film substrate, the transparent protective layer being a cured film made of a reactive resin containing a solvent-soluble fluorocopolymer having a fluorine content of 10% by weight or more in fluoroolefin units and having a hydroxyl group, and a polyisocyanate compound, and a heat-adhesive mark-forming layer provided by a coating method on and in contact with the protective layer, the heat-adhesive mark-forming layer being made of a thermoplastic polyol resin in which a metal oxide whose color tone changes when its oxidation number changes upon irradiation with an ultraviolet laser is dispersed, and a blocked polyisocyanate.
[0013] The second invention is a transfer sheet for a mark-forming member by ultraviolet laser, as described in the first invention, characterized in that the thermoplastic polyol resin is a solvent-soluble fluorocopolymer having a fluorine content of 10% by weight or more in fluoroolefin units and having a hydroxyl group.
[0014] The third invention is a transfer sheet for marking members using an ultraviolet laser, as described in the first and second inventions, characterized in that the metal oxide whose color tone changes as its oxidation number changes upon irradiation with an ultraviolet laser is titanium oxide.
[0015] The fourth invention is a transfer sheet for a mark-forming member by an ultraviolet laser, as described in claims 1, 2 and 3, characterized in that the mark-forming member by an ultraviolet laser is a mark-forming member used for process control of products that have an alkali treatment and / or acid treatment process. Effect of the Invention
[0016] The effects of the present invention are that it is possible to easily manufacture a mark-forming member for process control on which advanced information such as two-dimensional codes can be printed, which requires resistance to strong alkalies and strong acids at high temperatures after mark formation, and it is also possible to provide a transfer sheet for mark-forming members using an ultraviolet laser, which can be used as a variety of mark-forming members which require weather resistance, solvent resistance, stain resistance and heat resistance of 200°C or higher after mark formation. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0017] The present invention will be described in detail below. <<Thermoplastic resin film substrate>> The substrate used in the present invention may be a polyester film such as polyethylene terephthalate, polybutylene terephthalate, or polyethylene naphthalate, a polyamide film, a triacetyl cellulose film, a polymethylpentene film, a polycarbonate film, a polyurethane film, a polyolefin film such as polyethylene or polypropylene, or a polyvinyl chloride resin film. A polyethylene terephthalate film, a polybutylene terephthalate film, or the like is particularly preferred from the viewpoint of cost and heat resistance. These may be stretched or unstretched films. The thickness of the substrate used may be selected depending on the degree of surface unevenness of the transferee, the transfer conditions, and the type of substrate used, but it is usually preferable to use a film having a thickness of 5 to 100 μm. In addition, since the transparent protective layer described later needs to be peeled off from the thermoplastic resin film substrate, the film substrate may be provided with a release layer that can be removed with water or an alkaline aqueous solution after peeling, or a release layer made of a conventionally known adhesion regulator layer such as a silicone resin. In addition, when transferring the transfer sheet to the transfer recipient, in order to prevent melting due to the heat of the transfer roll and to provide lubricity, a conventionally known heat-resistant lubrication layer made of a silicone resin or the like may be provided on the back side of the substrate of the transfer sheet having the above-mentioned transfer layer.
[0018] <<Transparent protective layer>> The transparent protective layer used in the present invention is provided as a transparent cured film made of a solvent-soluble fluorocopolymer having a fluorine content of 10% by weight or more in fluoroolefin units and having a hydroxyl group, and a reactive resin containing a polyisocyanate compound, which is peelably provided on the thermoplastic resin film substrate, and is intended to exhibit not only resistance during coating of a thermally adhesive mark-forming layer whose color tone changes upon irradiation with an ultraviolet laser, as described below, but also various functions such as protective functions of chemical resistance such as alkali resistance and acid resistance, as well as heat resistance, antifouling property, weather resistance, etc., after mark formation of the mark-forming layer.
[0019] If the fluorine content in the fluoroolefin unit is less than 10% by weight, the resin will have poor resistance and will not achieve the object of the present invention. The fluorine content is usually 10-70% by weight, preferably 15-50% by weight. If the fluorine content exceeds 70% by weight, the resin will have poor solvent solubility. The hydroxyl value is preferably selected to be in the range of about 2-200, preferably 5-150.
[0020] Examples of solvent-soluble fluorocopolymers include polyvinylidene fluoride, tetrafluoroethylene-propylene copolymers, vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene copolymers, copolymers of fluoroolefins such as tetrafluoroethylene, chlorotrifluoroethylene, and hexafluoropropylene with ethylenically unsaturated compounds such as vinyl ethers, vinyl esters, allyl ethers, allyl esters, acryloyl compounds, and methacryloyl compounds. Particularly preferred examples include fluoroolefin-vinyl ether copolymers and fluoroolefin-vinyl ester copolymers. If necessary, resins such as acrylic polyols and organic modified silicones may be added. Examples of solvent-soluble fluorocopolymers that meet the requirements are commercially available from various companies, such as Lumiflon (trade name) manufactured by AGC Co., Ltd. and Zaflon (trade name) manufactured by Toagosei Co., Ltd.
[0021] The polyisocyanate compound for forming the cured film of the solvent-soluble fluorocopolymer having a hydroxyl group is preferably an aliphatic or alicyclic polyisocyanate compound or a silicone polyisocyanate compound from the viewpoint of preventing coloration of the cured film. Examples of the aliphatic polyisocyanate include hexamethylene diisocyanate (HDI), dimer acid diisocyanate (DDI), and norbornene diisocyanate (NBDI). Examples of the alicyclic polyisocyanate include isophorone diisocyanate (IPDI), dicyclohexylmethane diisocyanate (hydrogenated MDI, H12MDI), and hydrogenated XDI (H6XDI). Examples of the silicone polyisocyanate include X-48-1801, a product name of Shin-Etsu Chemical Co., Ltd. These compounds can be used alone or in combination. These polyisocyanate compounds may be blocked polyisocyanate compounds from the viewpoint of stability during coating.
[0022] The amount of polyisocyanate compound added to the hydroxyl group of the fluorocopolymer resin is preferably such that the molar equivalent ratio of the isocyanate group of the polyisocyanate compound to the hydroxyl group of the fluorocopolymer resin is 10:1 to 1:1. If the molar equivalent of the hydroxyl group of the resin is greater than 10:1 of the molar equivalent of the isocyanate group, the solvent resistance and protective film strength during coating of the thermal adhesive mark forming layer, which changes color tone upon irradiation with an ultraviolet laser, described below, become insufficient. In addition, if the molar equivalent of the isocyanate group is greater than 1:1 of the molar equivalent of the hydroxyl group of the resin, problems may occur in the chemical resistance and heat resistance, and unreacted isocyanate groups may remain after heat curing, causing stickiness of the film, etc.
[0023] The transparent protective layer used in the present invention must be provided on the thermoplastic resin film substrate in a peelable manner, including stability over time. As a method for making the transparent protective layer peelable, as described above, a release layer that can be removed with water or an alkaline aqueous solution after peeling or a release layer made of a conventionally known adhesion adjusting agent layer such as a silicone resin can be provided on the film substrate.
[0024] As another example of a method for not providing the peeling layer or release layer on the thermoplastic resin film substrate, the amount of the polyisocyanate compound added relative to the hydroxyl group of the fluorocopolymer resin is set within the specific range, and the polyisocyanate in the transparent protective layer is provided by adjusting the molar equivalent ratio of each isocyanate group of the aliphatic polyisocyanate and the alicyclic polyisocyanate, which is particularly suitable when the thermoplastic resin film substrate is a polyester film substrate such as a polyethylene terephthalate film or a polybutylene terephthalate film. This method is preferable from the viewpoint of cost and simplification of production.
[0025] Regarding the adjustment of the molar equivalent ratio of each isocyanate group of the aliphatic polyisocyanate and the alicyclic polyisocyanate, for example, it is preferable to use an aliphatic polyisocyanate such as hexamethylene diisocyanate (HDI) and an alicyclic polyisocyanate such as isophorone diisocyanate (IPDI) in a range of 1:0.5 to 1:3. If the molar equivalent of the isocyanate group of the aliphatic isocyanate is greater than the range of the molar equivalent of the isocyanate group of the alicyclic isocyanate, the adhesion to the substrate may become greater than necessary, and the substrate may become difficult to peel after transfer. In addition, if the molar equivalent of the isocyanate group of the alicyclic isocyanate is greater than the range of the molar equivalent of the isocyanate group of the aliphatic isocyanate, the adhesion to the substrate may become greater than necessary, and the handling property of the transfer sheet may become poor.
[0026] The transparent protective layer must be transparent enough to allow the ultraviolet laser used in the thermal adhesive mark forming layer described later to reach the layer, but the fluororesin coating of the present invention is easily transparent to the ultraviolet laser, so that the transparent protective layer is less damaged during mark formation, and the laser energy is mainly absorbed by metal oxides, etc., changing the oxidation number of the metal oxide, and only the color tone changes. However, inorganic or organic particles, etc. may be added to improve scratch resistance, etc., within a range that does not substantially impair the transparency.
[0027] The transparent protective layer is preferably coated to a thickness of 1 to 30 μm using a bar coater, a microcoater, a gravure coater, etc., and then heated at 200° C. or less or cured at 100° C. or less to form a hardened resin coating.
[0028] The specific effect of the transparent protective layer is that, in the selection of resins constituting the thermal adhesive mark forming layer described later, it is possible to use, for example, acrylic resins and polyester resins, which are ester compounds, that cannot withstand an alkali resistance evaluation alone, thereby expanding the selection of resins for the thermal adhesive mark forming layer. Furthermore, since the transparent protective layer of the present invention is made of a cured film, it is possible to use the same solvent when the thermal adhesive mark forming layer is applied in contact with the transparent protective layer, which has the advantage of expanding the selection of resins for the thermal adhesive mark forming layer. Furthermore, it is possible to realize the functions of antifouling and weather resistance.
[0029] <<Thermal adhesive mark forming layer>> The thermally adhesive mark formation layer used in the present invention is in contact with the transparent protective layer and comprises a thermoplastic polyol resin having dispersed therein a metal oxide whose color tone changes as its oxidation number changes upon irradiation with an ultraviolet laser, and a blocked polyisocyanate which reacts and crosslinks with the resin and the transfer target upon heating, and is required to have a thermal adhesion function including the transparent protective layer to the transfer target, heat resistance according to the purpose of use, a mark formation function by irradiation with an ultraviolet laser, etc.
[0030] The thermoplastic polyol resin used in the present invention is protected by the transparent protective layer from the viewpoint of resistance to strong alkali and strong acid, as described above. Therefore, when the protective layer is not present, it is possible to use polyester polyol resins, polycaprolactone polyol resins, (modified) acrylic polyol resins, etc., which are ester resins that could not be used under high temperatures of strong alkali or strong acid due to hydrolysis. In addition, a wide range of thermoplastic polyol resins, such as polyvinyl acetal resins, polyether polyol resins, polybutadiene modified to introduce hydroxyl groups, and the above-mentioned fluorine-based polyol resins, can be used. In addition, from the viewpoint of heat resistance, it may be selected according to the purpose of use, but when high heat resistance is particularly required, the use of the above-mentioned fluorine-based polyol resins is particularly preferred. In particular, in the case of fluorine-based polyol resins, by using the same binder for each layer, the adhesive strength between the layers is increased, and the transfer layer transferred to the transferee functions as a strong layer even if it is multi-layered. In addition, the thermoplastic polyol resin may be a resin in which a part of the thermoplastic polyol resin is replaced with another functional group reactive with an isocyanate group, such as an epoxy group.
[0031] The blocked polyisocyanate used in the present invention is an isocyanate curing agent which is substantially unreactive at room temperature, but is activated and reacts when heated to a temperature equal to or higher than the reaction initiation temperature. Various blocked polyisocyanates well known to those skilled in the art can be selected and used depending on the crosslinking reactive group possessed by the binder resin. For example, compounds in which a free isocyanate group contained in an isocyanate compound such as tolylene diisocyanate, xylylene diisocyanate, mesitylene diisocyanate, diphenylmethane diisocyanate, isophorone diisocyanate, or hexamethylene diisocyanate, or in a biuret, adduct, or isocyanurate thereof is blocked with a blocking agent such as a phenol-based blocking agent such as phenol or cresol, an oxime-based blocking agent such as methyl ethyl ketone oxime or acetone oxime, a lactam-based blocking agent such as ε-caprolactam or γ-butyrolactam, an active methylene-based blocking agent such as ethyl acetoacetate, acetylacetone, or ethyl malonate, an alcohol-based blocking agent such as methanol or ethanol, an amine-based blocking agent, an imine-based blocking agent, an imide-based blocking agent, an imidazole-based blocking agent, or a mercaptan-based blocking agent can be used.
[0032] The activation temperature of the blocked polyisocyanate is preferably from 50° C. to 200° C., and more preferably from 70° C. to 200° C. If the activation temperature of the blocked polyisocyanate, which is a latent curing agent, is less than 50° C., the blocking property of the transfer sheet during high-temperature storage is poor, and if the activation temperature exceeds 200° C., the baking temperature must be set high, resulting in poor productivity.
[0033] The ratio of the hydroxyl equivalent, which is the reactive group of the thermoplastic polyol resin in the heat-adhesive mark-forming layer, to the reactive group equivalent of the blocked polyisocyanate curing agent is preferably 1:0.4 to 1:2. If the reactive group equivalent of the blocked polyisocyanate curing agent is smaller than this range relative to the hydroxyl equivalent of the thermoplastic polyol resin, the adhesive strength with the transparent protective layer or the transfer target may decrease. If it is larger than this range, the curing agent may self-crosslink during curing, making the adhesive layer brittle and failing to provide a strong film.
[0034] The metal oxide used in the present invention, the color tone of which changes as the oxidation number changes upon irradiation with an ultraviolet laser, includes conventionally known metal oxides and metal hydroxides derived from metals selected from zinc, titanium, cerium, antimony, tin, iron and zirconium, among which titanium oxide is particularly preferred. The crystal structure of titanium oxide may be any of anatase type, rutile type and brookite type. Rutile type titanium oxide is preferred because of its good pigment dispersibility. Titanium oxide may also be titanium oxide coated with silica, alumina or the like. The average particle size of titanium oxide is preferably 10 to 500 nm, more preferably 50 to 400 nm. These titanium oxides promote discoloration of the ink coating by absorbing an ultraviolet laser in the 260 to 400 nm range, and exhibit excellent visibility in the ultraviolet laser printed portion. In addition, since the ultraviolet laser has an effect of obtaining excellent print visibility even with low energy output, a laminate using the ultraviolet laser marking composition can suppress damage (irregularities) at the laser irradiated portion, and a laminate with suppressed deterioration in appearance can be obtained.
[0035] The amount of the metal oxide used in the present invention in the heat-adhesive mark-forming layer must be within a range in which the change in color caused by irradiation with an ultraviolet laser can be sufficiently detected. If the amount is too large, the layer becomes brittle. From this viewpoint, the amount of the resin binder component and the metal oxide in the heat-adhesive mark-forming layer is preferably 5 to 70% by weight, more preferably 10 to 50% by weight, of the metal oxide relative to the total of the resin binder and the metal oxide.
[0036] The thermally adhesive mark-forming layer, which is essential to the present invention and is made of a metal oxide / thermoplastic polyol resin / blocked polyisocyanate crosslinking agent, is preferably coated to a thickness of 2 to 30 μm using a bar coater, microcoater, gravure coater, or the like, usually with a ketone-based and / or toluene-based solvent or the like.
[0037] <<Substrate of transfer material>> The heat-resistant substrate to which the transfer sheet for mark-forming member by ultraviolet laser is transferred may be a metal plate or processed plate such as a stainless steel plate, glass or glass nonwoven fabric, or a heat-resistant plastic film / plate / container. As for the form of the substrate, it is preferable that the substrate surface has a functional group such as a hydroxyl group, an amino group, a thiol group, or an epoxy group that reacts with an isocyanate group, or a functional group such as an isocyanate group that reacts with a hydroxyl group of the thermoplastic polyol resin of the thermal adhesive mark-forming layer, by surface treatment. For this reason, when a poorly adhesive substrate such as a stainless steel plate is used as the substrate, it is preferable to perform surface treatment with a silane coupling agent having the functional group, or to provide an anchor layer of a binder resin having the conventionally known crosslinkable functional group.
[0038] <<Transfer method onto a transfer substrate>> The surface of the heat-adhesive mark-forming layer of the transfer sheet is superimposed on the transferee, and the heat-adhesive mark-forming layer and the transparent protective layer are transferred by heat pressure, and then the thermoplastic resin film substrate is peeled off. The transferee from which the substrate has been peeled off is heated, and the blocked polyisocyanate, which is the latent curing agent in the heat-adhesive mark-forming layer, is thermally crosslinked with the thermoplastic polyol resin and the surface of the transferee, thereby forming a transfer coating on the surface of the transferee. The substrate may be peeled off after thermal crosslinking as necessary. In addition, in the case where the water-soluble release layer is present as described above, the release layer may be removed with water, and then the transferee from which the substrate has been peeled off may be thermally crosslinked. Alternatively, the release layer may be removed with water after the thermal crosslinking.
[0039] The transfer method is such that the thermal adhesive mark-forming layer is heated and a sufficient pressure can be applied by using a known laminator, heat press machine, printer having a thermal head, handy iron, hot rod, etc. Furthermore, the transparent protective layer and the thermal adhesive mark-forming layer are transferred to the transfer recipient, and a mark-forming member is provided on the transfer recipient, after which the mark-forming member is cured at a temperature of usually 200° C. or less, and the thermal adhesive mark-forming layer is sufficiently cured.
[0040] <<UV laser for mark formation>> In the present invention, the laser used for mark formation is not particularly limited as long as the wavelength of the laser light emitted from the laser light source is in the ultraviolet light region, but for example, the wavelength is within the range of 250 to 400 nm, preferably 320 to 380 nm. Examples of laser light sources capable of oscillating an ultraviolet laser include solid ultraviolet lasers with tripled (355 nm) or quadrupled (266 nm) waves, and various excimer lasers (XeF, XeCl, KrF, etc.). In view of the ease of obtaining the device, it is preferable to use a laser light source with a wavelength of 355 nm. The laser light source may be a laser array in which a plurality of laser light emitting elements are bundled. In addition, the mark formation by the ultraviolet laser may be performed before or after the thermal adhesive mark forming layer is sufficiently cured.
[0041] The present invention will be described in detail below with reference to examples, but the present invention is not limited to these examples.
[0042] <Transfer sheet 1> Transparent protective layer ink 1, consisting of a toluene solution of 100 parts by weight of fluoroethylene / alkyl vinyl ether copolymer (hydroxyl value: 52 mg KOH / g), 6.49 parts by weight of hexamethylene diisocyanate (NCO%: 10%), and 8.11 parts by weight of isophorone diisocyanate (NCO%: 8%), was applied to a thickness of 10 μm on a 12 μm thick polyester film using a microcoater. After application, the ink was left to dry at a temperature of 120°C for 10 minutes to form a hardened transparent protective layer. (The molar ratio of hydroxyl groups / isocyanate groups was 3 / 1, and the molar ratio of the isocyanate groups of aliphatic isocyanate / alicyclic isocyanate was 1 / 1.) Furthermore, on the transparent protective layer, a thermal adhesive mark forming layer ink 1 consisting of a toluene solution of 100 parts by weight of fluoroethylene / alkyl vinyl ether copolymer (hydroxyl value: 50 mg KOH / g), 53.5 parts by weight of blocked polyisocyanate (hexamethylene diisocyanate, NCO%: 10.5%, dissociation temperature: 140 to 160°C), and 100 parts by weight of titanium oxide was applied to a dry film thickness of 7 μm using a microcoater to obtain a transfer sheet 1.
[0043] <Transfer sheet 2> A transfer sheet 2 was obtained in the same manner as in Example 1, except that a thermal adhesive mark formation layer ink 2 consisting of a toluene solution of 100 parts by weight of acrylic polyol resin (hydroxyl value: 30 mg KOH / g), 32.1 parts by weight of blocked polyisocyanate (hexamethylene diisocyanate, NCO%: 10.5%, dissociation temperature: 140 to 160°C), and 108 parts by weight of titanium oxide was applied to the transfer sheet 1 in a dry film thickness of 5 μm using a microcoater.
[0044] <Transfer sheet 3> A transfer sheet 3 was obtained in the same manner as in Example 1, except that a thermal adhesive mark formation layer ink 3 consisting of a toluene solution of 100 parts by weight of thermoplastic saturated copolymer polyester resin (hydroxyl value: 46 mgKOH / g), 49.2 parts by weight of blocked polyisocyanate (hexamethylene diisocyanate, NCO%: 10.5%, dissociation temperature: 140 to 160°C), and 120 parts by weight of titanium oxide was applied to the transfer sheet 1 in a dry film thickness of 5 μm using a microcoater.
[0045] <Transfer sheet 4> A transfer sheet 4 was obtained in the same manner as in Example 1, except that in the transfer sheet 1, a transparent protective layer ink 2 consisting of a toluene solution of 100 parts by weight of fluoroethylene / alkyl vinyl ether copolymer (hydroxyl value: 52 mg KOH / g) and 13.0 parts by weight of hexamethylene diisocyanate (NCO%: 10%) was applied to a 12 μm thick polyester film having a silicone-based release layer.
[0046] <Transfer sheet 5> A water-soluble release layer having a dry thickness of 2 μm and made of polyvinyl alcohol:hydroxypropylmethylcellulose (weight ratio 6:4) was formed on a polyester film having a thickness of 12 μm, and on top of that, a thermal adhesive mark forming layer as described in transfer sheet 2 was formed in the same manner without providing the transparent protective layer, to obtain transfer sheet 5.
[0047] The transfer sheets 1, 2, 3, 4 and 5 were laminated on a 0.1 mm thick stainless steel plate provided with an epoxy primer, with the thermal adhesive mark forming layer surface overlapping the stainless steel plate, using a laminator machine having two pairs of rubber rolls with a rubber hardness of 80°, with the upper roll temperature set to 170°C, the lower roll temperature set to 150°C, and the roll pressure set to 4.0 kg / cm 2 The stainless steel plate with the transferred mark was cooled to room temperature, and then the substrate was peeled off and baked at 170°C for 30 minutes in a gear oven to obtain ultraviolet laser mark forming members 1, 2, 3, 4, and 5.
[0048] Thereafter, the polyester films of the mark-forming members 1, 2, 3, 4, and 5 were peeled off, and black two-dimensional codes were printed on the mark-forming members 1, 2, 3, 4 (Examples 1 to 4) and 5 (Comparative Example 1) with an ultraviolet laser (355 nm) manufactured by Keyence Corporation (product name: MD-U1000C), and the following adhesion and durability evaluations were performed on the mark-forming members. Note that, for the mark-forming member 5, the adhesion and durability evaluations were performed after the peeling layer was removed with an aqueous solution.
[0049] <Evaluation of adhesion and durability after mark formation> After the mark was formed by the ultraviolet laser, the adhesion, alkali resistance, acid resistance and heat resistance of the mark forming member were evaluated under the following conditions.
[0050] Adhesion evaluation: Cross-cut evaluation JIS H-8602
[0051] Alkaline resistance: A) Caustic soda concentration 9% by weight water / temperature 85°C / immersion time 60 minutes, and B) Evaluate the change in the mark formation surface under the conditions of 45% caustic soda water / temperature 90℃ / immersion time 150 minutes
[0052] Acid resistance: Hydrochloric acid concentration 20% / temperature 50℃ / immersion time 150 minutes, mark formation surface Evaluate the changes
[0053] Heat resistance: Evaluate changes in the marking surface under conditions of 260°C / heating time 30 minutes
[0054] The evaluation results of the mark forming members 1, 2, 3, 4 and 5 are shown in Table 1 as Example 1 (transfer sheet 1), Example 2 (transfer sheet 2), Example 3 (transfer sheet 3), Example 4 (transfer sheet 4), and Comparison Example 1 (transfer sheet 5).
[0055] [Table 1]
Claims
1. A transfer sheet for a mark-forming member using an ultraviolet laser, comprising: a transparent protective layer peelably provided on a thermoplastic resin film substrate, the transparent protective layer being a cured film of a reactive resin containing a solvent-soluble fluorocopolymer having a fluorine content of 10% by weight or more in fluoroolefin units and having a hydroxyl group, and a polyisocyanate compound; and a heat-adhesive mark-forming layer provided by a coating method on and in contact with the protective layer, the heat-adhesive mark-forming layer being made of a thermoplastic polyol resin having dispersed therein a metal oxide whose color tone changes when its oxidation number changes upon irradiation with an ultraviolet laser, and a blocked polyisocyanate.
2. 2. The transfer sheet for a member for forming a mark by an ultraviolet laser according to claim 1, wherein the thermoplastic polyol resin is a solvent-soluble fluorocopolymer having a fluorine content of 10% by weight or more in fluoroolefin units and having a hydroxyl group.
3. 3. The transfer sheet for a member for marking by an ultraviolet laser according to claim 1, wherein the metal oxide whose color tone changes as its oxidation number changes upon irradiation with an ultraviolet laser is titanium oxide.
4. A transfer sheet for a mark-forming member by an ultraviolet laser, as described in claim 1, claim 2, or claim 3, characterized in that the mark-forming member by an ultraviolet laser is a mark-forming member used for process control of a product that has an alkali treatment and / or acid treatment process.
Citation Information
Patent Citations
Coated material of fluororesin displaying scale, pattern, letter or the like and its production
JP1994100716A
Ultraviolet laser marking composition, and printed matter and laminate including the same
JP2020078924A